Asset-backed securities - Bhattacharya, Anand K.; Fabozzi, Frank J.; Prudential Securities Inc. (New Hope, Pa. : Frank J. Fabozzi Associates ; New York, N.Y. : Prudential Securities Incorporated, 1996)
Asset-Backed Securities provides comprehensive coverage of the major asset-backed securities, structuring issues, and relative value analysis from the leading experts in the field. Comprehensive coverage includes the expanding frontiers of asset securitization, introduction to ABS accounting, trends in the structuring of ABSs, and prepayment nomenclature in the ABS market.
Includes index.
oif 13/02/15
Loan
Keywords: Asset-backed financing; Securities